2021
DOI: 10.1038/s41598-021-95418-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal visual attention to simple social stimuli in 4-month-old infants at high risk for Autism

Abstract: Despite an increasing interest in detecting early signs of Autism Spectrum Disorders (ASD), the pathogenesis of the social impairments characterizing ASD is still largely unknown. Atypical visual attention to social stimuli is a potential early marker of the social and communicative deficits of ASD. Some authors hypothesized that such impairments are present from birth, leading to a decline in the subsequent typical functioning of the learning-mechanisms. Others suggested that these early deficits emerge durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Thus, it seems that simple objects with such motion features convey animacy perception in adults. Interestingly, this is also true in human newborns that can differentiate between self- and non-self-propelled objects (Di Giorgio et al 2017a , b ) as well as objects that change speed in different ways (Di Giorgio et al 2021a , b ). Such evidence suggests the existence of inborn predispositions to visual cues of motion that trigger animacy perception.…”
Section: Motion Drives Animacymentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, it seems that simple objects with such motion features convey animacy perception in adults. Interestingly, this is also true in human newborns that can differentiate between self- and non-self-propelled objects (Di Giorgio et al 2017a , b ) as well as objects that change speed in different ways (Di Giorgio et al 2021a , b ). Such evidence suggests the existence of inborn predispositions to visual cues of motion that trigger animacy perception.…”
Section: Motion Drives Animacymentioning
confidence: 95%
“…Compared to low-risk controls, high-risk newborns were more likely to look at nonanimate stimuli. Interestingly, in 4 months, the pattern was reversed as high-risk infants looked more at the stimuli representing animacy than low-risk infants did (Di Giorgio et al 2021a , b ). This is particularly intriguing as it suggests that the deficit in social predispositions might not be caused by the absence of an adequate mechanism but by a development delay in its activation.…”
Section: For a Better Understanding Of Human Typical And Atypical Cog...mentioning
confidence: 99%
See 1 more Smart Citation
“…The predisposed face perception is not a fixed trait, and the developmental changes need to be carefully examined (Simion and Di Giorgio, 2015). More recently, it has been reported that newborns with a high familial risk of ASD (6-10 days of age) show a reduced face preference when compared with low-risk controls (Di Giorgio et al, 2016a); also see Di Giorgio et al (2021a) for the follow-up longitudinal study on 4-month-old infants.…”
Section: Face-like Configurationmentioning
confidence: 99%
“…The characteristics of atypical social attention have also been reported in very young children without a definite diagnosis of ASD but instead at high familial risk for ASD who have not yet started speaking. For instance, infants at high familial risk for ASD have been observed to show differences in visual attention to social stimuli compared with low-risk infants as early as 1 week after birth, and these abnormalities persist at 4 months of age ( 12 , 13 ). In a study involving infants diagnosed with ASD at 6 months of age, a decrease in gaze toward people and faces within social scenes has been reported ( 14 ).…”
Section: Introductionmentioning
confidence: 99%